Works councils and workers' party preferences in Germany - Uwe Jirjahn; Thi Xuan Thu Le (British Journal of Industrial Relations, 2024)
Research on the consequences of works councils has been dominated by economic aspects. Our study provides evidence that works councils have non-financial consequences for society that go beyond the boundaries of the workplace. Using panel data from a large sample of workers in Germany, we show that works councils have an influence on workers' party preferences. Works council presence is negatively associated with preferences for extreme right-wing parties and positively associated with preferences for the Social Democratic Party and The Left. These results hold in panel data estimations including a large set of controls and accounting for unobserved individual-specific factors. Our findings fit the notion that workplace democracy increases workers' solidarity and their awareness of social and political issues. However, the influence of works council representation on party preferences is gender-specific. Asymmetric gender norms within society may entail a lower responsiveness of women's party preferences to workplace democracy.
Keywords: 330